Perspsi Guru Kelas Sekolah Dasar Penyelenggara Pendidikan Inklusif terhadap Anak Berkebutuhan Khusus - Septiana Andriani; Mega Iswari (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is motivated by the teacher's perception or teacher's view of children with special needs in schools providing inclusive education. The teacher's perception will greatly affect the learning process in schools. This study aims to determine the views of classroom teachers in primary schools providing inclusive education to children with special needs in Kampar Regency. Aspects of perception that are described are in the form of teacher knowledge of children with special needs and teacher attitudes towards children with special needs. The method used is descriptive quantitative research using data collection techniques in the form of distributing questionnaires to teachers as respondents. Determination of the sample using totally sampling technique. Data analysis using percentage calculation technique. The results of this study indicate that most teachers (56.72%) have a good understanding of children with special needs and most teachers (77.14%) have a good attitude towards children with special needs.